Ventilation of denervated transplanted lung at risk for overdistention by reverse triggering and breath stacking: a role for the paradoxical reflex of Head. Comment on Br J Anaesth 2022; 129: e1e4 - Santa Cruz, Roberto (2023)
Fil: Santa Cruz, Roberto. Instituto Universitario de Ciencias de la Salud. Fundación Barceló; Argentina.